2019
DOI: 10.1136/emermed-2018-207781
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of triage systems for paediatric emergency care: a systematic review

Abstract: ObjectiveTo present a systematic review on the reliability of triage systems for paediatric emergency care.MethodsA search of MEDLINE, Cochrane Library, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online, Nursing Database Index and Spanish Health Sciences Bibliographic Index for articles in English, French, Portuguese or Spanish was conducted to identify reliability studies of five-level triage systems for patients aged 0–18 years published up to April 2018. Two revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…222 49113 4433 (38) 40 49149 (42) Janajati 2546 (44) 1068 (47) 932 (42) 193 (43) 117 4644 5031 (38) 161 (46) Dalit 507 (9) 219 (10) 193 (9) 30 719 78 ( Presentation to ED, n (%)* 08:00-16:00 weekdays 1037 (24) 481 (28) 322 (19) 96 2837 2023 (38) 24 (40) 54 2216:00-08:00 or holidays 465 (27) 567 (34) 76 (22) 56 3019 3217 (28) 67 (27) ICU or OT or Referred 341 (8) 126 7117 726 826 1418 307 1221 ( Other complaints included musculoskeletal, neurology, urinary, cardiovascular diseases or complaints, psychology, and other general complaints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…222 49113 4433 (38) 40 49149 (42) Janajati 2546 (44) 1068 (47) 932 (42) 193 (43) 117 4644 5031 (38) 161 (46) Dalit 507 (9) 219 (10) 193 (9) 30 719 78 ( Presentation to ED, n (%)* 08:00-16:00 weekdays 1037 (24) 481 (28) 322 (19) 96 2837 2023 (38) 24 (40) 54 2216:00-08:00 or holidays 465 (27) 567 (34) 76 (22) 56 3019 3217 (28) 67 (27) ICU or OT or Referred 341 (8) 126 7117 726 826 1418 307 1221 ( Other complaints included musculoskeletal, neurology, urinary, cardiovascular diseases or complaints, psychology, and other general complaints.…”
Section: Resultsmentioning
confidence: 99%
“…The RETTS triage system was developed in Sweden and has been increasingly used in the Scandinavian countries. [17][18][19] Pediatric emergency triage system was recently systematically assessed, 38 and only one of the 18 studies of triage system reliability identified in the systematic review 38 was from a LIC. 39 Thus, the present report of triage priority categories in a pediatric population in a low income setting is unique.…”
Section: Pediatric Triage In Lmicmentioning
confidence: 99%
“…In a systemic review of reliability of various triage protocols for emergency pediatric patients, studies Interhospital transfer 32 (0. 20 On the other hand, studies for various ambulance dispatch protocols revealed the validation specific conditions such as stroke, acute coronary syndrome, outof-hospital cardiac arrest, and trauma. [21][22][23][24][25][26][27] Based on these previous studies, we selected hospitalization as a measure to assess the validity of telephone triage protocol in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indicators for assessing the validity of triage protocol are controversial. In a systemic review of reliability of various triage protocols for emergency pediatric patients, studies used the agreement of triage nurses and pediatric emergency medicine physicians as an indicator of the reliability of triage protocol 20 . On the other hand, studies for various ambulance dispatch protocols revealed the validation specific conditions such as stroke, acute coronary syndrome, out‐of‐hospital cardiac arrest, and trauma 21–27 .…”
Section: Discussionmentioning
confidence: 99%
“…Correct use of the RETTS‐p requires extensive training and experience. RETTS‐p has only been tested for reliability, not validity (Henning et al., 2016; Magalhaes‐Barbosa et al., 2019; Westergren et al., 2014).…”
Section: Methodsmentioning
confidence: 99%